Impact of Power Sector Reform on Operational Efficiency in Abuja Electricity Distribution Company - Muhammad , Isa (Kashere Journal of Politics and International Relations, 2024)
Inadequate generation transmission and distribution of electricity constitute major bottlenecks to productivity and industrial growth in Nigeria. Over the years, several reforms have been implemented in the power sector but the challenges persist, and many socio-economic activities are negatively impacted. The problems are exacerbated by inconsistent policies of the government on the management of the power sector and the inefficient capacity of the private operators. This research aims to explore the impact of power sector reform on operational efficiency in Abuja Electricity Distribution Company, involving 50,631 respondents with a sample size of 367 determined using the Krejcie and Morgan table. Data collection utilized a self-structured questionnaire, and analysis employed descriptive statistics like frequency count and mean. The study is anchored on the modernization theory. The findings showed that the power sector reform in Abuja Electricity Distribution Company (AEDC) has revealed challenges related to poor funding, inadequate implementation of reforms, and lack of essential infrastructure. The study recommends establishing a robust oversight mechanism, involving regulatory bodies and industry experts, which is crucial for ensuring the effective implementation of power sector reforms. This oversight can monitor and evaluate the progress, identify bottlenecks, and recommend corrective measures, fostering a more streamlined and efficient execution of reforms. Implementing diverse funding mechanisms, such as public-private partnerships, attracting investments, and securing government support, can bolster AEDC's financial position. This would provide the necessary resources to upgrade infrastructure, invest in advanced technologies, and improve overall operational capabilities.